ANALYSIS ON SENTENCE PATTERNS IN THAI STUDENTS’ ESSAY - Putri Kurniawan Aprilia (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This current research focused on analyzing sentence patterns and words formation in seventh grade students’ essay. This study used descriptive qualitative research method. The participant were thirty five students at Eakkapap Sasanawich Islamic School Krabi Thailand. The data was obtained from the eassys made by seventh grade students. The result of this research showed that the affixation on the writing results of the seventh grade students indicated that form of prefix word used only re-. While the most widely form of the suffix word was suffix –ed in the verb category (past tense and past participle), suffix –ing in the noun (gerund) and verb (present participle) category, and suffix –s/-es in the noun plural category. The after one is that the sentence structures found are simple sentences consisting of several variations, such as 1) Subject-Verb (SV), 2) Double Subject-Verb (SSV), 3) Double Subject and Verb (SSVV), and 4) Subject-Double Verb (SVV). There were also several passive voices. The compound sentence, complex sentence, and compound-complex sentence structure were also found in the seventh grade students’ essays.